Kedudukan Klaim BPJS Ketenagakerjaan Sebagai Harta Waris Dalam Perspektif Hukum Islam - Saleha, Saleha; Mulida Hayati; Syamhudian Noor (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the normative discrepancy between the BPJS Employment claim mechanism and the principles of Islamic inheritance law, as well as to propose a model for harmonizing the distribution of claims in a fair manner. The main problem lies in the discrepancy between the linear nature of BPJS administrative regulations and the imperative nature of Islamic inheritance law, which has the potential to disregard the rights of legitimate heirs (faraidh). The method used is normative legal research with a normative juridical approach that focuses on the synchronization of norms in the Qur'an, Hadith, and social security regulations in Indonesia. The results of the study show that there are differences in legal status for each program: Old Age Security (JHT) claims are categorized as inheritance (al-tirkah) that must be divided according to faraidh provisions, while Death Security (JKM) and Work Accident Security (JKK) claims are considered gifts or tabarru’ whose distribution follows the participant's designation for the benefit of the family. The novelty of this research lies in the proposed Claim Distribution Synchronization Model, which fills the regulatory void by distinguishing between the legal treatment of accumulated savings funds and compensation funds. The practical implications of this research encourage BPJS institutions and policymakers to reorient the claim distribution mechanism to be in line with the principles of Islamic family law in order to minimize conflicts among heirs and ensure legal certainty for the muslim community in Indonesia. Penelitian ini bertujuan untuk menganalisis ketidaksinkronan normatif antara mekanisme klaim BPJS Ketenagakerjaan dengan prinsip hukum waris Islam serta menawarkan model harmonisasi distribusi klaim yang berkeadilan. Masalah utama terletak pada diskrepansi antara regulasi administratif BPJS yang bersifat linier dengan hukum waris Islam yang bersifat imperatif, sehingga berpotensi mengabaikan hak ahli waris sah (faraidh). Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan yuridis normatif yang berfokus pada sinkronisasi norma dalam Al-Qur'an, Hadis, dan regulasi jaminan sosial di Indonesia. Hasil penelitian menunjukkan adanya perbedaan status hukum pada setiap program: klaim Jaminan Hari Tua (JHT) dikategorikan sebagai harta peninggalan (al-tirkah) yang wajib dibagi berdasarkan ketentuan faraidh, sedangkan klaim Jaminan Kematian (JKM) dan Jaminan Kecelakaan Kerja (JKK) bersifat hibah atau tabarru’ yang distribusinya mengikuti penunjukan peserta demi kemaslahatan keluarga. Kebaruan penelitian ini terletak pada usulan Model Sinkronisasi Distribusi Klaim yang mengisi kekosongan regulatif dengan membedakan perlakuan hukum antara dana akumulasi tabungan dan dana santunan. Implikasi praktis penelitian ini mendorong lembaga BPJS dan pembuat kebijakan untuk mereorientasi mekanisme distribusi klaim agar selaras dengan prinsip keadilan hukum keluarga Islam guna meminimalisir konflik ahli waris dan menjamin kepastian hukum bagi masyarakat muslim di Indonesia.